Síntese de enaminonaftoquinonas derivadas da lausona com atividade anticâncer - Cadorini, Mayara Archanjo (2020)
Cancer is a general term used for a group of diseases that are characterized by the uncontroled growth, division and proliferation of a group of cells that can spread to other regions of the body through a process known as metastasis, which is the cause o